Co‐designing resources to support older people with intellectual disabilities and their families plan for parental death and transitions in care - Rebecca Anderson‐Kittow; Richard Keagan‐Bull; Jo Giles; Irene Tuffrey‐Wijne (Wiley, 2024)
Abstract Background Older people with intellectual disabilities and their families report a lack of support for planning for parental death and transitions in care. This article aims to demonstrate the process of co‐designing resources to support older people with intellectual disabilities and their families to plan for the future. Methods Following interviews and focus groups with older people with intellectual disabilities and their families, we used an adapted experience‐based co‐design process to develop planning ahead resources. This included a 'trigger film' summarising findings from the earlier interview study, 12 co‐design workshops and a user feedback phase. Results The co‐design group developed a set of 102 'Planning Ahead Cards' to help families to talk about the future and prepare for meetings with social care professionals. The group made decisions about the content, format and design of resources, and how co‐design workshops would run. The user feedback phase led to changes to the cards, and families and stakeholder groups suggested that they would be useful for planning ahead. Conclusion The Planning Ahead Cards may facilitate planning for parental death and transitions in care for older people with intellectual disabilities and their families. The co‐design approach was key to ensuring that the resources were useful and accessible for families. Patient or Public Contribution People with intellectual disabilities and their families contributed to the design of the resources through the co‐design workshops and feedback phase. The research team includes a research assistant with intellectual disabilities who co‐facilitated co‐design workshops and co‐authored this article.